Cardiac catheterization: nurse's assistance to patients in the prevention of complications (Research, Society and Development, 2022)
Cardiac catheterization is an invasive procedure in which a catheter is introduced into peripheral arteries or veins with the aim of confirming the presence of artery obstructions or evaluating the functioning of the valves. Therefore, the research aims to describe the complications facing cardiac catheterization and identify the nurse's assistance to patients in the prevention of these complications. This is exploratory descriptive research with a qualitative methodological approach, using the Integrative Literature Review (INR) as a technique, together with the PICO strategy to prepare the guiding question. The research was carried out between April and May 2022 in the databases indexed in the Virtual Health Library (BVS): BDENF, MEDLINE and LILACS, through the combination of three Health Sciences Descriptors (DeCS) crossed with the Boolean operator “AND”: “Cardiac catheterization”; "Nursing"; “Patient care”, 392 articles were found, 128 in MEDLINE, 142 in LILACS and 122 in BDENF. By adding the inclusion and exclusion criteria, the number was reduced to 63. After the analysis, 10 publications were selected. The performance of angiography allows the localization of coronary obstructions, the assessment of their extension and severity, complementing the stratification of their prognosis and identifying the most appropriate form of treatment. In this context, it is expected that this research can serve as a subsidy to guide new studies, where the actions carried out by the nursing team corroborate to reduce these conditions that interfere in the quality of life of patients with cardiac catheterization.